2022
DOI: 10.1177/21582440221104811
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association and Influencing Factors of Job Satisfaction and Burnout Among Nurses in Macao

Abstract: The factors affecting nursing job satisfaction and burnout have been widely studied, but the research results vary in nations with different cultures and organization schemes. The healthcare system of Macao is unique, which tends to be a combination of that of Chinese and Portuguese. This study aimed to assess the factors influencing job satisfaction and burnout and to investigate their associations with demographic characteristics. This descriptive cross-sectional study was conducted among 345 randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Kovner et al in their study showed that factors related to the work environment were significantly related to job satisfaction. More than 40.0% of the variation in satisfaction was explained by various attitudes at work: supervisor support, workgroup cohesiveness, work diversity, autonomy, organizational constraints, promotion opportunities, work and family conflict and fairness (38), which has been confirmed by other studies (28,39,40). In our study, the mean score of all areas of work life in the surveyed group was 3.09 ± 0.45 (max.…”
Section: Discussionsupporting
confidence: 88%
“…Kovner et al in their study showed that factors related to the work environment were significantly related to job satisfaction. More than 40.0% of the variation in satisfaction was explained by various attitudes at work: supervisor support, workgroup cohesiveness, work diversity, autonomy, organizational constraints, promotion opportunities, work and family conflict and fairness (38), which has been confirmed by other studies (28,39,40). In our study, the mean score of all areas of work life in the surveyed group was 3.09 ± 0.45 (max.…”
Section: Discussionsupporting
confidence: 88%